Impact of Telephonic Reinforcement on Glycemic Control in Pediatric Type 1 Diabetes Mellitus: A Prospective Interventional Study at a Tertiary Healthcare Center - Reemu Bansal; Ambi Katyayani; Bala C. Bethamcherla; Lakshiya Ramamoorthy; Rajiv Ranjan; Lakshmi Murugesan; Nithila Sivakumar; Darshan K. Raj; Rishabh Jain (Journal of Pharmacy and Bioallied Sciences)
Introduction: Type 1 Diabetes Mellitus (T1DM) is a prevalent endocrine disease in children, requiring consistent management of diet, physical activity, insulin delivery, and glucose monitoring. Telemedicine has shown benefits for adults with chronic diseases, but its effectiveness for pediatric T1DM in India is less explored. This study compares glycemic control in pediatric T1DM patients before and after telephonic reinforcement. Methodology: A prospective interventional study was conducted at a tertiary healthcare center in India. Thirty-five pediatric T1DM patients were included, with baseline characteristics recorded. Patients received telephonic support three times a month for nine months, focusing on blood sugar monitoring, insulin administration, and follow-ups. Data were analyzed using paired t-tests with a significance level of P < 0.05. Results: The mean HbA1c level decreased significantly from 11.85 ± 1.15 at baseline to 9.05 ± 1.55 at nine months (P < 0.001). Conclusion: Telephonic reinforcement improved glycemic control and compliance in pediatric T1DM patients. Further studies with larger sample sizes are needed to validate these findings.